Open-ended Experiments in Developing Cognitive Abilities - Gangoli, S.G.; Gurumurthy, C. (SCHOOL SCIENCE, 2013)
Laboratory activities play a very important role in Physics instruction because they are aimed to develop: (i) Scientific knowledge, cosnceptual understanding and ability to apply scientific knowledge to life-situations. (ii) Skills—organisational, manipulative, communicative and constructional. (iii) Creative ability, intellectual ability, problem solving techniques, processes of Science, curiosity to know ’why’, ’what’ and ’how’ of thing, belief in cause and effect relationships, impartial judgements, etc. Efforts are continuously made all over the world to improve laboratory instruction. Many are of the opinion that approaches emphasising some amount of divergent thinking and openness in the activities are more advantageous than the traditional approach to promote the above objectives. Accordingly, we have been working on open-ended approach for doing Physics experiments and examining its effectiveness by field tests.